Diakonia Sosial Transformatif Karismatik - Yusup Rogo Yuono (Sekolah Tinggi Teologi Borneo, 2022)
Abstract: Poverty is a complex and long-standing humanitarian problem. The church has theresponsibility to realize the Kingdom of God on earth, is present to provide attention and answers tothis problem. This research examines related to efforts to develop social services to overcome povertyproblems based on charismatic transformative social services. The method used in this research isdescriptive qualitative which describes the existing phenomena, to then be analyzed using descriptiveanalysis. The charismatic group believes that transformative social services with charismaticcharacteristics are effective for efforts to reduce poverty. It is hoped that the results of thedevelopment of charismatic transformative social services can be used by charismatic churches intheir efforts to overcome poverty.Keywords: social service, diakonia, charismaticAbstrak: Kemiskinan adalah masalah kemanusiaan yang kompleks dan sudah lama ada. Gerejamempunyai tanggung jawab mewujudkan Kerajaan Allah di muka bumi, hadir memberikanperhatian dan jawaban terhadap masalah ini. Penelitian ini mengulas terkait dengan usahapengembangan pelayanan sosial untuk menanggulangi masalah kemiskinan berdasarkan pelayanansosial transformatif karismatik. Metode yang dipakai dalam penelitian ini adalah deskriptif kualitatifyang menggambarkan fenomena yang ada, untuk kemudian dianalisis menggunakan analisisdesktiptif. Kelompok karismatik percaya pelayanan sosial transformatif yang bercirikan karismatikefektif bagi upaya penanggulangan kemiskinan. Hasil dari pengembangan pelayanan sosialtransformatif karismatik ini diharapkan dapat dipakai oleh gereja-gereja karismatik dalam kiprahnyamenanggulangi kemiskinan.Kata kunci: pelayanan sosial, diakonia, karismatik